2001
DOI: 10.1038/sj.ejcn.1601217
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nutritional folate status and selected vitamin status of women of childbearing age

Abstract: Objective: The aim of the study was to investigate folate and other selected vitamin status (ascorbic acid, tocopherol, retinol, vitamin B 12 ), haematological indices and total homocysteine concentration of serum in women of childbearing age. Design: A cross-sectional study. Setting: Warsaw. Subjects: Healthy women aged 18 -30 y (n ¼ 78) not pregnant presently or previously, and not taking drugs. Results: Haemoglobin and haematocrit values according to WHO criteria for 18 to 30-y-old women were normal. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
4
13
0
Order By: Relevance
“…The results of our study also showed lower levels of serum vitamin B 12 (194 pmol/l) in the women compared to French, Italian, Mexican, West African [31] , Costa Rican [36] , Polish [34] and Bangladeshi [29] women ( table 4 ).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The results of our study also showed lower levels of serum vitamin B 12 (194 pmol/l) in the women compared to French, Italian, Mexican, West African [31] , Costa Rican [36] , Polish [34] and Bangladeshi [29] women ( table 4 ).…”
Section: Discussionmentioning
confidence: 64%
“…The mean serum folate of the women in our study (13.6 nmol/l) was higher than that of women in Bangladesh [29] , Sri Lanka [30] , France and Italy [31] , but lower than the mean serum folate of women in the UK [32] , Mexico [31] , Croatia [33] and Gambia [32] . However, the mean serum folate of Iranian women was close to the mean se- [34] . The mean serum homocysteine concentration of the Iranian women (12.6 mol/l) was much higher compared to British, Gambian [32] , French, Italian and Mexican women [31] ; it was also higher than in women from Sri Lanka [30] , but lower than in West African women [31] ( table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chile deserves special mention with a successful wheat flour fortification program that has been evaluated recently and resulted in an important decrease of folic acid deficiency (Bunout et al, 1998;Hertrampf et al, 2003). Other countries such as Spain, Cuba and Poland, with important socioeconomic differences, are affected by a high prevalence of folic acid and vitamin B 12 deficiencies (OPS, 1999;Wartanowicz et al, 2001;Planeéis et al, 2003). In Venezuela, there is a high prevalence of folic acid deficiency for all groups analyzed, although vitamin B 12 levels also require immediate action not only due to megaloblastic anemia problems but also the fact that this deficiency is considered an independent risk factor for neural tube defects, due to a reduced cellular uptake of folates in the presence of vitamin B 12 deficiency (Allen, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Bearing in mind the proposals of Wartanowicz et al ( 27 ), serum folate concentra-tions of Ͻ 6.8 nmol/L were understood to reflect a high risk of folate deficiency, while values of Ն 14.9 nmol/L were understood to represent optimum status. The upper limit for homocysteine was taken as 10.4 mol/ L, in agreement with the proposal of Tucker et al ( 28 ) for the female population.…”
Section: Methodsmentioning
confidence: 99%